Estudio de los tiempos de ejecución para agregar valor a los procesos administrativos de la empresa Crisomar S.A. - Chávez Leones, Adrián José (2016)
The present investigation had as objective to carry out a study of execution times to add value to the administrative processes of the company Crisomar S.A., for which quantitative methods were used, inductive and descriptive, which allowed the correct execution of the same, the results obtained were: Phase 1 lifting of the processes of the company Crisomar S.A. of the town of San Vicente, this phase allowed to establish the threads that are developed in the company which are: generate roles of payment, control of income and outgoings and preform. Phase 2. Definition of the tool for the measurement of the execution times of administrative processes. It is done through the application of a bibliographic review by which it was determined that the ideal tool to use was the timing. Phase 3. Analysis of the time spent in the execution of the tasks for the improvement of administrative processes. Set the time spent in the process were calculated optimal times, average times, times, and Times type and thus identified the thread that represented the bottleneck that was the generate roles of payments to workers. Phase 4. Proposal for improvements to the use of execution times in administrative processes, there were two proposals that would allow it to effectuate the processes, the first was the implementation of a accounting software, the second consists of the implementation of a format in Excel for the generation of roles of payments.